Periodontal problems following surgical extraction of impacted mandibular third molar teeth - Majid Eshghpour; Reza Shah Akbari; Amir Hossein Nejat (Mashhad University of Medical Sciences, 2013)
Introduction:There are conflicting reports on the effects of surgical removal of impacted mandibular third molars on the periodontium of the adjacent teeth. The aim of this study was to compare the condition of the periodontium six months after extraction of impacted mandibular third molars with baseline values. Methods: Fifty patients with mesioangular impacted mandibular third molarsparticipated in this study. Probing depth (PD), Leo and Sillness' gingival index (GI), and clinical attachment level (CAL) in distobuccal, mid-distal, and distolingual surfaces of second molar teeth were assessed before surgical extraction of the third molars and 6 months later. To evaluate the changes in alveolar bone height (BH), two parallel PA radiographs obtained at the baseline and follow-up session. Data was analyzed with SPSS 11.0 software atthe confidence interval of 95%. Results: Thirty-eight females and 12 males participated in this study. Twenty-eight(56%) of impacted molar teeth were in the right side and 22 (44%) were in the left side. Baseline values of PD, CAL, and GI at three points of the distal surface of the mandibular second molar tooth had no significant differences with follow-up values (P-value> 0.05). According to the radiographs, baseline BH also had insignificant difference with follow-up height (P-value>0.05). Conclusion: Surgical removal of impacted mandibular third molar does not affect periodontium after 6 months.